ASSESSMENT OF CANINE NEWBORN VIABILITY BY UMBILICAL VEIN LACTATE EVALUATION AND ITS PROGNOSTIC VALUE IN SHORT TERM NEONATAL SURVIVAL - JAYAKUMAR, C; KRISHNASWAMY, A; SUDHA, G; HONNAPPA, T G (The Indian Journal of Animal Reproduction, 2016)
The present study estimated umbilical vein lactate (UL) in healthy puppies, and the puppies stressed due to difficult whelping as well as the association of UL with neonatal viability status and the duration of labor. Umbilical veinlactate in puppies from dystocic deliveries was higher (p<0.05) compared to those delivered by spontaneous whelping.The pups delivered through emergency cesarean had highest UL (12.99±2.02 mmol/l) and pups born by electivecesarean had lowest UL (4.08±0.84 mmol/l, p<0.05). Highest UL was recorded in puppies delivered of labor durationexceeding 12 h. A clear demarcation of UL at birth between surviving and dead puppies at 24 and 48 h was evidentand the puppies with UL d”8.0±0.24 mmol/l survived by day 14. In brief, umbilical vein lactate is a useful prognosticindicator for the assessment of survival of newborn p.uppies.